[Large painting of a woman in Celtic costume and a wolfhound titled "A Dia Saor Éire"] (1917)
[Photograph of large painting of a woman in Celtic costume and a wolfhound titled "A Dia Saor Éire]
Photograph placed in envelope with note in Irish regarding a "Mrs. Little" inscribed
Keywords: Ireland -- History -- 1910-1921; Photographic prints -- Irish -- 20th century